An examination of major works for wind band: “National emblem march” by Edwin Eugene Bagley ed. by Frederick Fennell, “On an American spiritual” by David Holsinger, “Portraits” by Jim Colonna, “Serenade, Op. 22 (c)” by Derek Bourgeois. - Bistline, Michael E. (Kansas State University, 2009)
The following report is an in depth research and analysis project based on the graduation requirement for a Masters in Music Degree from Kansas State University. The product of this project was a conducting recital performed by Michael E. Bistline with the Union High School Concert Band. This performance was held on May 5, 2009 in Matt Auditorium at Union High School. The repertoire included National Emblem March by E.E. Bagley/edited by Frederick Fennell, On An American Spiritual by David Holsinger, Portraits by Jim Colonna, and Serenade Op. 22 (c) by Derek Bourgeois. The theoretical, historical and technical analyses of this project was collected using the Unit of the Teacher Resource Guide, developed by Richard Miles and the Macro, Micro, Macro score analysis form developed by Dr. Frank Tracz. This report also includes documentation of the planning and evaluation of each rehearsal.
Keywords: Analysis of "National Emblem March" By E.E. Bagley Edited By Frederick Fennell; Analysis of "On An American Spiritual" By David Holsinger; Analysis of "Portraits" By Jim Colonna; Analysis of "Serenade Op 22 (c)" By Derek Bourgeois; Education, Music (0522)